BUSINESS CLUSTERS AND THE POTENTIAL OF THE BIOTECHNOLOGY SECTOR IN LITHUANIA - Giedraitis, Vincentas R.; Notten, Tom; Rastenienė, Aušra (Ekonomika, 2009)
What are the unique circumstances that allow innovations in an economy to take hold and mature into productive business sectors? We pose the given question in our discussion of the uncommonly favorable circumstances surrounding the biotechnology sector in Lithuania. The purpose of this paper is to analyze Lithuania’s ability to expand its economy during a time of crisis, focusing on its unique ability to innovate in such sectors as biotechnology. Our primary hypothesis is as follows: Lithuanian biotechnology sector is expanding because business clusters have been established. Drawing upon Schumpeter’s ideas of innovation and Porter’s business cluster theory, we argue that Lithuania is “at the right place and the right time” to make itself a regional leader in biotechnology. We draw upon the world-systems theory to argue that biotechnology is one means whereby Lithuania can rise in the global core-periphery hierarchy.